Understanding Knowledge as a Commons: From Theory to Practice - Jane Duffy (Issues in Science and Technology Librarianship)
This article reviews the book Understanding Knowledge as a Commons: From Theory to Practice, Charlotte Hess and Elinor Ostrom (eds).